Estimating genotype-environment interactions for internal fruit quality traits in cherry tomatoes (2020)
Genotype-environment interactions (GEI) were assessed in 10 cherry tomato accessions in nine environments, including four artificial settings (0, 60 120, and 180 kg ha-1 of potassium) established on the experimental farms Montelindo (Palestina), Tesorito (Manizales), and CEUNP (Palmira) (Colombia). The plant material included 10 cherry tomato genotypes obtained from the germplasm bank at the Instituto Agronómico de Campinas and Tomato Genetics Resources Center (TGRC). A completely randomized block design with four blocks corresponding to the level of potassium fertilization was used (0, 60, 120, 180 kg ha-1); 0 kg ha-1 was the level reported for the soil. The effective size of the experiment unit was seven plants; the plot included the five central plants. A distance of 1.5 m between rows, 0.50 m between plants, and 2 m between blocks was used. The contents of soluble solids (°Brix), vitamin C (mg/100 g fresh weight), and lycopene (µg g-1 fresh weight) were assessed. The analysis of variance (ANOVA) showed significant differences (P<0.01) between the tomato genotypes, environments, and G×E interactions for the three assessed traits . The AMMI analysis identified similar and contrasting environments and determined the genotypes that contributed the most to the GEI. The environments with 120 and 180 kg ha-1 potassium favored the expression of vitamin C, while Palmira favored the lycopene content. The findings are useful for identifying optimal locations and elite genotypes that can be used as sources of variability in fruit quality improvement programs for cherry tomatoes.